sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

New tools for old problems — comparing drone- and field-based assessments of a problematic plant species - Jens Oldeland; Rasmus Revermann; Jona Luther-Mosebach; Tillmann Buttschardt; Jan R. K. Lehmann (Environmental Monitoring and Assessment, 2021)
Plant species that negatively affect their environment by encroachment require constant management and monitoring through field surveys. Drones have been suggested to support field surveyors allowing more accurate mapping with just-in-time aerial imagery. Furthermore, object-based image analysis tools could increase the accuracy of species maps. However, only few studies compare species distribution maps resulting from traditional field surveys and object-based image analysis using drone imagery. We acquired drone imagery for a saltmarsh area (18 ha) on the Hallig Nordstrandischmoor (Germany) with patches of Elymus athericus , a tall grass which encroaches higher parts of saltmarshes . A field survey was conducted afterwards using the drone orthoimagery as a baseline . We used object-based image analysis (OBIA) to segment CIR imagery into polygons which were classified into eight land cover classes. Finally, we compared polygons of the field-based and OBIA-based maps visually and for location, area, and overlap before and after post-processing. OBIA-based classification yielded good results (kappa = 0.937) and agreed in general with the field-based maps (field = 6.29 ha, drone = 6.22 ha with E . athericus dominance). Post-processing revealed 0.31 ha of misclassified polygons, which were often related to water runnels or shadows, leaving 5.91 ha of E . athericus cover. Overlap of both polygon maps was only 70% resulting from many small patches identified where E . athericus was absent. In sum, drones can greatly support field surveys in monitoring of plant species by allowing for accurate species maps and just-in-time captured very-high-resolution imagery.

A sharp floristic discontinuity revealed by the biogeographic regionalization of African savannas - Adeline Fayolle; Michael D. Swaine; Julie Aleman; Akomian F. Azihou; David Bauman; Mariska te Beest; Emmanuel N. Chidumayo; Joris P. G. M. Cromsigt; Hélène Dessard; Manfred Finckh; Francisco Maiato P. Gonçalves; Jean‐Francois Gillet; et al. (Journal of Biogeography, 2019)
Aim In tropical Africa, savannas cover huge areas, have high plant species richness and are considered as a major natural resource for most countries. There is, however, little information available on their floristics and biogeography at the continental scale, despite the importance of such information for our understanding of the drivers of species diversity at various scales and for effective conservation and management. Here, we collated and analysed floristic data from across the continent in order to propose a biogeographical regionalization for African savannas. Location We collated floristic information (specifically woody species lists) for 298 samples of savanna vegetation across Africa, extending from 18° N to 33° S and from 17° W to 48° E. Taxa We focused on native woody species. Methods We used ordination and clustering to identify the floristic discontinuities and gradual transitions across African savannas. Floristic relationships, specificity and turnover, within and between floristic clusters, were analysed using a (dis‐)similarity‐based approach. Results We identified eight floristic clusters across African savannas which in turn were grouped into two larger macro‐units. Ordinations at species and genus levels showed a clear differentiation in woody species composition between the North/West macro‐unit and the South/East macro‐unit. This floristic discontinuity matches to the High (i.e. N&W) and Low (S&E) division of Africa previously proposed by White ( ) and which tracks climatic and topographical variation. In the N&W savannas, the floristic gradient determined by rainfall was partitioned into the Sudanian (drier) and Guinean (wetter) clusters. Within the highly heterogeneous S&E savannas and woodlands, six clusters were identified: Ugandan, Ethiopian, Mozambican, Zambezian, Namibian and South African. Main conclusions The proposed pan‐African classification of savannas and woodlands might assist the development of coordinated management and conservation policies.

Habitat at the mountain tops: how long can Rock Ptarmigan (Lagopus muta helvetica) survive rapid climate change in the Swiss Alps? A multi-scale approach - Rasmus Revermann; Hans Schmid; Niklaus Zbinden; Reto Spaar; Boris Schröder (Journal of Ornithology, 2012)